2016
DOI: 10.4238/gmr.15038277
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key biomarkers involved in osteosarcoma using altered modules

Abstract: ABSTRACT. The aim of this study was to screen for key biomarkers of osteosarcoma (OS) by tracking altered modules. Protein-protein interaction (PPI) networks of OS and normal groups were constructed and re-weighted using the Pearson correlation coefficient (PCC), respectively. The condition-specific modules were explored from OS and normal PPI networks using a clique-merging algorithm. Altered modules were identified by a maximum weight bipartite-matching method. The important biological pathways in OS were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…It is worth mentioning that Liu et al have concluded that FEN1, identified as a key gene associated with OS development, might be a potential biomarker for diagnosis and treatment of this tumor by systematically tracking the altered modules in the reweighted normal and OS PPI networks. 28 In the present study, we found that osteosarcoma patients, who showed high expression of FEN1, had shorter OS time and PFS time. Meanwhile, multivariate analysis indicated that FEN1 expression was an independent prognostic factor for osteosarcoma patients.…”
Section: Discussionsupporting
confidence: 53%
“…It is worth mentioning that Liu et al have concluded that FEN1, identified as a key gene associated with OS development, might be a potential biomarker for diagnosis and treatment of this tumor by systematically tracking the altered modules in the reweighted normal and OS PPI networks. 28 In the present study, we found that osteosarcoma patients, who showed high expression of FEN1, had shorter OS time and PFS time. Meanwhile, multivariate analysis indicated that FEN1 expression was an independent prognostic factor for osteosarcoma patients.…”
Section: Discussionsupporting
confidence: 53%
“…These tumors are typically rapid growers with high metastatic potential, especially to the lungs and bones (5). Although treatment with surgery and neoadjuvant chemotherapy appears to cure 60%-70% of cases (6), the 5-year survival rate Research investigating the mechanism of osteosarcoma development has primarily focused on chromosomal abnormalities, genetic alterations of tumor suppressor genes, activation of oncogenes and dysregulation of major signaling pathways (12). Therefore, the exact role of CUL1 in the tumorigenesis and progression of osteosarcoma has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Research investigating the mechanism of osteosarcoma development has primarily focused on chromosomal abnormalities, genetic alterations of tumor suppressor genes, activation of oncogenes and dysregulation of major signaling pathways (12). Therefore, the exact role of CUL1 in the tumorigenesis and progression of osteosarcoma has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Subunit G3: Subunit G3 is expressed in kidney and rat epididymis 105 , 109 . Its protein is used as a novel immunohistochemical marker for differentiating subtypes of chromophobe renal cell carcinoma (RCC) including clear cell, papillary RCCs 114 , 115 , and osteosarcoma 116 .…”
Section: Subunits Of V-atpase and Bone Diseasesmentioning
confidence: 99%